(untitled) (The Pakistan Development Review, 2000)
Economic Growth has posed an intellectual challenge ever since the beginning of systematic economic analysis. Adam Smith claimed that growth was related to division of labour, but he did not link them in a clear way. After that Thomas Malthus developed a formal model of a dynamic economic growth process in which each country converge toward stationary per capita income. According to this model, death rates fall and fertility rises when income exceed the equilibrium, and opposite occur when incomes are less than that level. Despite the influence of the Malthusian model in nineteenth century economists, fertility feel rather than rose as income grew during the past 150 years in the west and other parts of the world. The Neoclassical growth model of Solow (1956), which has been for the past thirty years the central framework to account for economic growth, focuses on exogenous technical population factors that determine output-input ratios, responded to the failure of Malthusian model.